Mental Health and Wellness Changing Mindsets for Effective Governance (African Journal of Public Administration & Management, 2026)
Mental health is a state of well-being in which an individual realizes their abilities, can cope with normal life stresses, work productively, and contribute to their community — WHOCommon Mental Health Issues in Africa:• - Depression and anxiety disorders• - Substance and alcohol use disorders• - Post-traumatic stress (from conflict, poverty, and disaster)• - Burnout and workplace-related stress• - Youth and gender-based mental health vulnerabilities (A 2024 meta-analysis across African countries found that roughly 27–30% of adolescents experience significant psychological distress• WHO reports that African women are twice as likely as men to experiencedepression, yet men are three to four times more likely to die by suicide
Keywords: Effective Governance; wellness; mental health; mindsets